Liquidated and ascertained damages (LAD) and requirements of mitigation - Yong, Mei Lee (2006)
When a project is late in completion due to contractor’s fault, the employer is entitled to a contractual remedy by enforcing the Liquidated and Ascertained Damages (LAD) provisions. However, contractors often seek to challenge the enforceability of LAD by alleging that the employers suffer no loss and that they are under a duty to mitigate their losses. Therefore, the objectives of the research are to determine the requirements of mitigation and the extent of the employer’s duty to mitigate his losses when enforcing his right under the LAD clause. The objectives of this research are achieved by analysing relevant laws governing LAD and mitigation. The governing laws include relevant statutes, judicial decisions, and the Contracts Act 1950. The research found that although the requirements is silent in standard forms of contract, an employer is bound to comply with the requirements of mitigation in enforcing LAD by taking all reasonable steps to mitigate his losses. Furthermore, employer’s duty to mitigate his losses is governed by the principles of mitigation. He is only bound to take all reasonable steps in order to comply with the requirements and does not has to embark on hazardous or uncertain courses of action that will cause him incur substantial expense or inconvenience, damage his reputation, or breach any contracts, in order to mitigate. The reasonable actions to mitigate will be determined on a case-to-case basis. In short, this research is expected to grab the attention of employers in enforcing LAD, so that they can safeguard their claims